PERTUMBUHAN DAN HASIL BEBERAPA KULTIVAR PADI GOGO LOKAL PADA JENIS PUPUK KANDANG YANG BERBEDA - Nugraha, Gede Teguh; Samudin, Sakka; Nursalam, Nursalam (AGROTEKBIS, 2019)
The research aimed to find local upland rice cultivar which has better growth and yield responses under the application of various manure and to find manure which has better effect on the growth and yield of local upland rice cultivars. This research was conducted at the Screen House of Faculty of Agriculture, Tadulako University of Palu, and lasted from September 2017 until January 2018. This research was arranged in a two-factorial completely randomized design. The first factor consisted of three cultivars of upland rice i.e. Kalendeng, Logi, and Uva Buya, while the second factor consisted of four types of manure i.e. with no manure addition (control), cow manure, chicken manure and goat manure each at a rate of 20 ton ha-1 or 73 g polybag-1. It was found that the Logi cultivar produced better growth and yield than the other cultivars whereas chicken manure resulted in better growth and yield of the upland cultivars.